Ruch w mieście czy miasto w ruchu? Dialektyka miejskiego rytmu = Motion in the city or the city in motion? Dialectics of urban rhythm - Rosińska, Monika (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The dynamic and at times ephemeral ("experimental") structure of this text is intended to serve primarily as a rhetorical device. In the first part, I use three archetypal figures that "travel" the city. These are: flaneur, situationist urban drift, and flaneuse. They exemplify moving around the city from an individual, idiosyncratic perspective. The second part of the text is a reconstruction of the gradual and systematic introduction of architecture/city into motion. The first part should be read in the context of the second and vice versa, so the reader is invited to read the text "dialectically".
Keywords: miasto; ruch; rytm